DIPLOMASI PROFETIK (STUDI ANALISIS PADA LAWATAN CHENG HO DI NUSANTARA) - Abid Rohman; HM Munir Mansyur (UNIDA Gontor, 2022)
This study is a literature study using a descriptive qualitative approach. The method used is content analysis with a historical study approach on historical documents of Zheng He's visit to the archipelago in the 14th-15th centuries AD. From the results of the discussion, this study concludes; first; The main mission of Zheng He's visit to the archipelago was to gain recognition from the rulers of the archipelago's kings of the Chinese emperor's power during the Ming Dynasty, as well as efforts to meet the logistical needs of the kingdom through trade and friendship and peace. Second; Zheng He's arrival in the archipelago contributed to the opportunity for good diplomatic relations between Indonesia and China today. This can happen, supported by the romantic factor of the beautiful history of the past that has been inscribed by Admiral Cheng Ho from China who has successfully carried out diplomatic missions and the symbols of Islam well in this archipelago. One of the evidences of these memories is the existence of several mosques in the archipelago whose architecture imitates the characteristics of China, namely the Muhammad Cheng Ho Mosque in several cities in Indonesia to commemorate Cheng Ho's services in carrying out diplomatic missions that were carried out peacefully.